METODE MENGAJAR DALAM AL-QUR’AN KAJIAN SURAT AN-NAHL AYAT 125 - As'ad As'ad (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
In addition to objectives and materials, there are also three important elements that can not be ignored in the learning process. These three elements are methods, tools or learning media, and evaluation. Method is a way that can be used by teachers in delivering learning materials to learners. In Arabic the method is called al-Tariqah. This word other than interpreted to the method, it is also interpreted to a path that can be taken in delivering the subject matter. Al-Qur’an al-karim, in conveying divine messages, using various methods, tools, or media. Indeed, al-Qur’an also speaks of the importance of evaluation. One’s faith has not been recognized or confirmed before being evaluated or tested.Keywords: The Teaching Method, in the Qur'an, Surah An-Nahl